Spontaneous Abortions and Gestational Diabetes Mellitus- A Study from Pakistan - Aasia Kanwal; Asma Salam; Aisha Bashir (Journal of Shalamar Medical & Dental College, 2021)
Background: Gestational diabetes mellitus leads to adverse pregnancy outcomes.